(untitled) (International Seminar of Islamic Counseling and Education Series Proceeding, 2025)
The increase in unemployment among college graduates is caused by several factors. The skills learned in college do not match the needs of the job market, as students are overly idealistic in their job search, and many jobs require specialized skills not taught in formal education. This study aims to determine the contribution of career adaptability to students’ work readiness during the school-to-work transition. This study used a quantitative descriptive approach with correlational methods. A total of 210 students selected using incidental sampling techniques participated in this study. The instruments used were the career adaptability and work readiness scales. The results showed that students’ career adaptability was in the high category, and their work readiness was in the medium category. The contribution of career adaptability to students’ work readiness was 24.1% (R = 0.491), and career adaptability, collectively, contributed 27.5% (R = 0.535) to students’ work readiness during the school-to-work transition. This study has implications for future researchers in helping students develop work readiness during the school-to-work transition